Learn Ncert All Solutions

from a handpicked tutor in LIVE 1-to-1 classes

from a handpicked tutor in LIVE 1-to-1 classes

# Find and correct the errors in the statement: (2x)^{2 } + 4(2x) + 7 = 2x^{2 }+ 8x + 7

**Solution:**

An equation is a mathematical statement with an 'equal to' symbol between two algebraic expressions that have equal values.

Given,

(2x)^{2 } + 4(2x) + 7 = 2x^{2 }+ 8x + 7

Solving LHS we get,

(2x)^{2} + 4(2x) + 7

= 4x^{2} + 8x + 7

But RHS = 2x^{2 }+ 8x + 7

Thus, L.H .S. ≠ R.H.S.

The correct statement is (2x)^{2} + 4(2x) + 7 = 4x^{2} + 8x + 7

**☛ Check: **NCERT Solutions for Class 8 Maths Chapter 14

**Video Solution:**

## Find and correct the errors in the statement: (2x)²^{ }+ 4(2x) + 7 = 2x²^{ }+ 8x + 7

Class 8 Maths NCERT Solutions Chapter 14 Exercise 14.4 Question 7

**Summary:**

Find and correct the errors in the statement: (2x)^{2 } + 4(2x) + 7 = 2x^{2 }+ 8x + 7. The correct statement is (2x)^{2} + 4(2x) + 7 = 4x^{2} + 8x + 7

**☛ Related Questions:**

- Find and correct the errors in the statement: (2x)2 + 5x = 4x + 5x = 9x
- Find and correct the errors in the statement: (3x + 2)2 = 3x2 + 6x + 4
- Find and correct the errors in the following mathematical statement. Substituting x = -3 in (a) x2+ 5x + 4 gives (-3)2 + 5(-3) + 4 = 9 + 2 + 4 = 15 (b) x2 - 5x + 4 gives (-3)2 - 5(-3) + 4 = 9 - 15 + 4 = -2 (c) x2 + 5x gives (-3)2 + 5(-3) = -9 - 15 = -24
- Find and correct the errors in the statement: (y - 3)2 = y2 - 9

Math worksheets and

visual curriculum

visual curriculum